Detection system for electro-separation analytical methods - Stohl, Radek; Glovinová, Eliska; Pospíchal, Jan (Journal of separation science, 2005)
The paper provides information about the on-line monitoring of components analysed by capillary electrophoresis. For this purposes we developed a whole-capillary transverse scanning detection system, which helps to improve and control the separation processes. A picture from a colour line scanner was used as a source of basic information for autonomous control of the separation process by regulation of the high voltage source. The application and algorithms for machine vision were designed in the progressive graphic development system LabVIEW. Real-time control of the separation process was implemented in a compact control process logic controller. The performance of the detection system was evaluated and the function of the overall system was tested by performing isotachophoretic analysis of a model mixture.